2021
DOI: 10.1080/13546783.2021.1979651
|View full text |Cite
|
Sign up to set email alerts
|

Increasing climate efficacy is not a surefire means to promoting climate commitment

Abstract: People's perception of their own efficacy is a critical precursor for adaptive behavioural responses to the threat posed by climate change. The present study investigated whether components of climate efficacy could be enhanced by short video messages. An online study (N ¼ 161) compared groups of participants who received messages focusing on individual or collective behaviour. Relative to a control group, these groups showed increased levels of response efficacy but not self-efficacy. However, this did not tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The results showed that more than half of the respondents believed the above-mentioned media may be beneficial to facilitate the formation of a classification habit [ 22 ]. Gu et al (2020) and Angill-Williams and Davis (2021) found that direct, simple expressions, e.g., embedding typical environmental crises in public service advertisements, including water scarcity, global warming, etc., can help improve the individual’s self-learning effect and express a more pro-environmental attitude [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that more than half of the respondents believed the above-mentioned media may be beneficial to facilitate the formation of a classification habit [ 22 ]. Gu et al (2020) and Angill-Williams and Davis (2021) found that direct, simple expressions, e.g., embedding typical environmental crises in public service advertisements, including water scarcity, global warming, etc., can help improve the individual’s self-learning effect and express a more pro-environmental attitude [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%